Analysis of the Antioxidant Activity of Young and Mature Bidara Leaves Using 2,2-Diphenyl-1-Picrylhydrazyl (DPPH) and Phytochemical Screening Test - Alvelin Bunga Kurniawati; Gatra Ervi Jayanti; Majida Ramadhan; Dian Novita Wulandari; Ike Widyaningrum (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
This study aimed to compare the antioxidant activity of young and mature bidara leaves using the DPPH method and to identify the content of secondary metabolites through phytochemical testing. Antioxidant activity was measured using the IC50 parameter, which represents the concentration of the extract that can capture 50% of DPPH free radicals. The test results showed that mature bidara leaves had an IC50 value of 34.984 ppm, indicating vigorous antioxidant activity, while young leaves had an IC50 value of 100.327 ppm, classified as moderate activity. Phytochemical testing revealed that both types of leaves contained alkaloids, saponins, and tannins, while flavonoids and triterpenoids were only found in old leaves. These results suggest that variations in secondary metabolite content, influenced by leaf age, contribute to differences in antioxidant activity. Thus, older bidara leaves are more potent as an antioxidant source compared to younger leaves. This study supports the utilization of bidara plants in the pharmaceutical industry and the development of traditional medicine based on natural ingredients.